Digitalisasi Pada UMKM “Tak Jemu-Jemu” Sebagai Hasil Kegiatan Studi Independen Di PT. Narasumber Teknologi Indonesia - Agustina, Tias; Muchtolifah, Muchtolifah; Perdana, Putra (Jurnal Ilmiah Wahana Pendidikan, 2023)
UMKM are driving the wheels of the economy in various regions in Indonesia because UMKM creates many jobs for the surrounding community. UMKM has great potential in driving an economy. With the existence of UMKM, the people who will participate in economic activities will also be even greater. Digitization for UMKM can facilitate the development of the UMKM sector in Indonesia coupled with government support to support the digitalization of UMKM can help UMKM actors to advance their businesses. UMKM Tak Jemu-Jemu is an UMKM that produces herbal drinks with a more modern composition of ingredients and packaging. UMKM products "Tak Jemu-Jemu" are herbal drinks with a combination of jelly toppings which are produced from selected herbal ingredients and are produced and packaged in a more modern way. The Digitization Process in Unfinished UMKM as a result of independent study activities at PT. This Indonesian Technology resource person has made the Tak-Jemu-Jemu UMKM, which were technically and operationally still conventional, to become digital by utilizing the lessons and practices that have been obtained during the independent study period.